Greening Electricity More Than Necessary: On the Excess Cost of Overlapping Regulation in EU Climate Policy - Christoph Böhringer; Knut Einar Rosendahl (University of Oldenburg, Department of Economics, 2010)
After the failure of the United Nations climate change conference at Copenhagen the EU is under domestic pressure to justify ambitious unilateral emissions reduction targets. Cost efficiency of EU-wide emission abatement becomes increasingly important in order to sustain EU leadership in climate policy. We argue that administered EU targets for renewable energies are doomed to make emission reduction much more costly than necessary and therfore could rather hinder than promote public support to unilateral action.
Keywords: D61; H21; H22; Q58; 330; EU Climate Policy; Emission Quotas; Green Quotas; Overlapping Regulation